A young-onset frontal dementia with dramatic calcifications due to a novel CSF1R mutation. Issue 3 (3rd May 2016) - Gore, Ethan; Manley, Andrew; Dees, Daniel; Appleby, Brian S.; Lerner, Alan J.
ABSTRACT: Neuroimaging and genomic analysis greatly aid in the identification of young-onset dementia antemortem. We present the case of a 33-year-old female with a 2-year rapid decline to dementia and immobility marked by personality change, executive deficits including compulsions, attention deficit, apraxia, Parkinsonism, and pyramidal signs. She had unique and dramatic calcifications and confluent white matter changes on imaging and was found to have a novel mutation in the colony stimulating factor 1 receptor gene causing adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP). Here, we review ALSP and briefly discuss differential diagnoses.